THE ABORIGINAL PEOPLES ACT 1954 AND THE RECOGNITION OF ORANG ASLI LAND RIGHTS (UUM Journal of Legal Studies, 2015)
The prevailing view about the Orang Asli’s occupation of land and access to forest resources are that they are ‘privileges’ extended by the states or at the governments’ discretion. It is widely believed that the Orang Asli live on the State land as tenant-at-will. This paper proposes to examine the position of the Aboriginal Peoples Act 1954 (Act 153) (the APA) and trace its historical background. It takes both historical and doctrinal approaches in the legal research methodology. Situated within this historical background, the principle that developed from it and the position of the laws, the paper argues that under the principle of respect to the rights of the existing inhabitants, the law recognizes the rights of the Orang Asli to their land and resources that arose from their custom and practice. The APA establishes a framework to recognize and protect these rights. There is no legal basis for the perception that the Orang Asli live on the State land on the benevolence of the State. Keywords: Legal history; Aboriginal Peoples Act 1954; Indigenous peoples; Orang Asli; Peninsular Malaysia.